Tinjauan Pelaksanaan Penyusutan Rekam Medis Di Rumah Sakit Umum Daerah Kembangan - Intan Rusdiana Dewi; Lily Widjaja; Laela Indawati; Noor Yulia (Jurnal Rumpun Ilmu Kesehatan, 2023)
Shrinkage is the reduction of medical records on storage shelves by moving inactive medical records to a different room from the active shelf seen from the last patient visit. The purpose of this study was to determine the implementation of shrinkage at the Kembangan Regional General Hospital. This research method uses a qualitative descriptive method by means of interviews and observations in the medical records unit. So it can be concluded from the results of the study that the Kembangan Regional General Hospital already has SOP related to shrinkage which is divided into SOP sorting, media transfer and destruction. In the implementation of shrinkage, officers carry out the process of sorting, transferring and transferring media every day. But officers do not conduct an assessment based on use value. The destruction process is carried out when the number of medical records has reached 2 tons by using a third party to make medical records in the form of pulp. The main obstacles to the implementation of shrinkage are officers who do not have a decree on duties and teams so that officers often delay the implementation of shrinkage, paper quality that makes it difficult for officers to see medical record sheets in the past year and scan machines that heat up quickly due to continuous use. Therefore, the Kembangan Regional General Hospital should complete the SOP related to shrinkage, make a decree of duties and conduct an assessment stage so that the implementation of shrinkage is carried out properly, and add a scan machine so that the implementation of media transfer is not delayed.